Comparative kinematic analysis of passing hurdle technique on Lui Jing: elite Chinese female hurdle athlete - Li, X.; Li, J. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: According to the literature, although much research on the kinematics of the hurdle technique for female athletes has taken place, the majority of studies pay greater attention to horizontal comparative analysis and analysis of techniques during competition for individuals [4]. The authors of this study have done some work on LIU Jing`s technical training over the past two years. The results of elite Chinese female hurdle athletes using LIU Jing`s technique improved quickly. This is a comparative analysis of technique from training programs to provide a reference for coaches during the winter season. Methods A 3D fixed-point shooting method was used in this experiment. Two high-speed cameras (Basler abozfc) are used with a screen frequency is 100 frames per seconds. The axis angle between the two planes is 75 °. The technique when passing the third hurdle in the test match before winter training commenced is recorded and is analyzed by 3-DSignal TEC V10c (filtering frequency is 8 Hz). A comparative analysis on kinematical data of this test and a test from the same time last year was conducted. Results Through a comparative analysis on the current technique of LIU Jing with her past technique, a number of conclusions were made. Findings were a small trunk angle and lower center of gravity during hurdling. Analysis also revealed the attacking hurdle legs folded insufficiently and an improved action of the swinging leg after passing a hurdle.